Pengembangan multimedia interaktif berbantu wordwall pada materi suku kata untuk meningkatkan literasi membaca dan motivasi belajar siswa sekolah dasar - OKTAVIA (Caruban: Jurnal Ilmiah Ilmu Pendidikan Dasar, 2024)
The problem currently being faced by schools in Indonesia is the minimal availability of software for learning in the form of interactive multimedia. In learning activities, educators still use a lot of printed media such as textbooks, modules, LKPD. In addition, educators have not been able to create and develop interactive multimedia learning software that can make students not only pay attention to the media or objects, but are also required to interact during learning. .The aim of this interactive multimedia is to make it easier for teachers to deliver easy and interactive teaching materials. Meanwhile for students it can increase reading literacy and learning motivation. The development method with ADDIE consists of stages: 1) Analysis, 2) Design, 3) Development, 4 ) Implementation, 5) Evaluation. The data collection process was carried out through interviews, observations and questionnaires. Research results from media tests were 88.5% in the "very high" category, material expert tests were 89.3% in the "very high" category, test small group trial, student response to interactive multimedia 97.5%, large group trial student response to interactive multimedia 90%, small group learning motivation trial 90%, large group learning motivation trial 87%. Small group reading pretest percentage 13, 53% and posttest 87.92%, there was an increase of 74.38%. The percentage of small group reading pretest was 15.05% and posttest was 89.44%, there was an increase of 74.39%. So it can be concluded that the development of interactive multimedia with the help of wordwall is very feasible, so that reading literacy and student learning motivation increases.